Comparison of the Effectiveness of Short-Term Solution-Focused Therapy and Compassion-Focused Therapy on Self-Efficacy in Married Women - Kheirkhah , Masoumeh; Bolghan-Abadi, Mustafa; Pourheydari , Sepideh (Mental Health and Lifestyle Journal, 2025)
The present study was conducted to compare the effectiveness of short-term solution-focused therapy and compassion-focused therapy on self-efficacy in married women. The research method was experimental, using a pretest-posttest-follow-up design with a control group. The statistical population consisted of all married women who referred to the Hazrat Zainab Cultural Center in Mashhad during the 2022–2023 academic year. The sample included 60 women selected through convenience sampling and randomly assigned to three groups of 20 participants each. The instrument used in this study was the General Self-Efficacy Questionnaire by Sherer et al. (1982). The short-term solution-focused therapy was conducted in six 90-minute sessions using the Diamond model, while the compassion-focused therapy sessions followed Gilbert’s (2014) protocol and included twelve 90-minute sessions held weekly. The control group was placed on a waiting list. A pretest was administered before the intervention, a posttest after the sessions, and a follow-up assessment was conducted two months later. During the course of the intervention and assessments, two participants from both the control group and the solution-focused therapy group dropped out, along with four participants from the compassion-focused therapy group. The data were analyzed using SPSS-27 software and repeated measures analysis of variance (ANOVA). The findings revealed that in the posttest and follow-up phases, there were statistically significant differences between the experimental groups (compassion-focused therapy and solution-focused therapy) and the control group. The results indicated that both therapeutic approaches were effective in enhancing self-efficacy in married women and had lasting effects (p < .05); however, there was no significant difference in the effectiveness between the two approaches.